Research approaches to describe the mechanisms of injuries in sport: limitations and possibilities - Krosshaug, T.; Andersen, T. E.; Olsen, O. E.; Myklebust, G.; Bahr, R. (British Journal of Sports Medicine, 2005)
A number of different methodological approaches have been used to describe the inciting event for sports injuries. These include interviews of injured athletes, analysis of video recordings of actual injuries, clinical studies (clinical findings of joint damage are studied to understand the injury mechanism, mainly through plain radiography, magnetic resonance imaging, arthroscopy, and computed tomography scans), in vivo studies (ligament strain or forces are measured to understand ligament loading patterns), cadaver studies, mathematical modelling and simulation of injury situations, and measurement/estimation from "close to injury" situations. In rare cases, injuries have even occurred during biomechanical experiments. This review describes each research approach and assesses its strengths and weaknesses in contributing to the understanding and prevention of sports injuries.